John Dunlop and the Quest for ConsensusA review of Dispute Resolution: Negotiation and Consensus Building by DunlopJohn T., Dover, MA: Auburn House, 1984, 296 pp., $24.95, hard bound. - Jacobs, David (Academy of Management Review, 1986)
The article presents a review of the book “Dispute Resolution: Negotiation and Consensus Building,” by John T. Dunlop.